Primary cutaneous mucinous carcinoma: A rare case report - K N Roopa; Meena N Jadhav; Shreekant K Kittur; Gajanan A Pise (Wolters Kluwer Medknow Publications, 2020)
Primary cutaneous mucinous carcinoma is a rare slowly growing neoplasm showing predilection for the head and neck, particularly the eyelids. On occasion, it affects other sites including scalp, face, ear, axillae, thorax, abdomen, groin, foot, hand, and vulva. Fewer than 150 cases have been reported in the literature. A 70-year-old man presented with an asymptomatic raised lesion over the left side of the face for 1 year. Microscopically, the diagnosis of primary cutaneous mucinous carcinoma was made, which was later confirmed by immunohistochemistry. Mucinous carcinoma of the skin has a relatively good prognosis with rare distant metastases, but has risk of local recurrence. Diagnosing it and differentiating it from metastatic carcinoma helps the clinician in further management of the patient.